Effect of health seeking interval on outcome in swine flu cases attended a tertiary care hospital in southern Rajasthan region of India - Sharma, Shalabh; Singhal, Yogesh Kumar (International Journal Of Community Medicine And Public Health, 2019)
Background: Swine flu influenza is an infection by H1N1 type of swine influenza virus. Swine influenza virus or swine-origin influenza virus (SIV or S-OIV) is a strain of the family of influenza viruses that’s endemic in swine (pigs). Early diagnosis and treatment is key approach to control the morbidity and mortality associated with swine flu which can be achieved by improving health seeking behaviour of community. Understanding of behaviour of community is essential for planning strategies for prevention and control. Aim of this study is to establish a relation between healthcare interval and outcome of swine flu. Methods: A complete data of all the patients visiting swine flu OPDs, swine flu wards and ICU were maintained for year 2015. Each patient visiting either the swine flu OPD or the swine flu ward, who was suspected clinically to be H1N1 positive were tested for real time PCR. Data was collected in a standardized pre-structured questionnaire. Results: Out of 1247 samples tested for rt-PCR, number of patients found to be swine positive was 491 (39.37%). Total 267 patients were admitted in swine flu ward and ICU, out of them 62 was expired. Clinical care intervals of more than 5 days from onset of symptoms to swab collection, diagnosis and admission were more in female and rural population. Mean duration between onset of symptom to hospitalization, swab collection and diagnosis was significantly higher in deceased patients than survived. Conclusions: Early presentation to healthcare facility is associated with better prognosis and outcome. After patient report to the health care setup, early sample collection and diagnosis help to reduce mortality.